Transfer Learning Community: Overcoming Transfer Shock and Increasing Retention of Mathematics and Science Majors. (November 2017) - Scott, Timothy P.; Thigpin, Sara S.; Bentz, Adrienne O.
The College of Science at Texas A&M University developed a transfer student learning community with one 2-year institution after receiving National Science Foundation funds for scholarships to support students majoring in engineering and science. To date, 89% of the students that matriculated to Texas A&M University under this grant have completed their degrees or are on target to do so. Eighty-three percent of historically underrepresented students supported through the grant have completed their degrees. Lessons learned from success of the grant have been implemented to create a mandatory learning community for every incoming transfer student. Hallmarks of the program include an Academic Boot Camp prior to the start of the semester and monthly meetings. Monthly meetings include intentional advising, campus resources, academic policies, access to peer mentors, and introduction to undergraduate research opportunities. Overall retention rates to the university have risen through this expanded learning community, as have overall grade point averages.